Produksi Enzim Selulase Kasar dari Isolat Bakteri B2S8 menggunakan Substrat Brangkasan Jagung dengan Perlakuan Konsentrasi Inokulum dan Komposisi Media yang berbeda - Purba, Nursatria; Gunam, Ida Bagus Wayan; Wijaya, I Made Mahaputra (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2020)
The purpose of this study was determined the media and concentration of cellulolytic bacterial isolates to produce high cellulase enzyme activity. Production of crude cellulase enzyme in media and concentration of different bacterial isolate used a factorial Randomized Block Design (RBD) which consist of two factors. The first factor was the media production of different cellulase enzyme consisting of 3 levels, namely media 1, 2 and 3. The second factor was the concentration of bacterial isolate consisting of 5 levels namely 1, 2, 3, 4 and 5%. This study used a B2S8 cellulolytic bacterial isolate that has the highest value of cellulase enzyme activity and the highest degradation rate of cellulose in previous studied and determined the ability of exoglucanase enzyme activity, endoglucanase enzyme and dissolved protein content produced from cellulolytic bacterial isolate. This study used Carboxymethyl Cellulose (CMC) for enzyme activity test and 1% corn stover as a substrate on the media to produce crude cellulase enzyme. The result showed that the highest cellulase enzyme activity in the third media and 5% cellulolytic bacterial inoculum concentration resulted in endoglucanase activity of 0.0332 IU/mL, exoglucanases enzyme activity of 0.0060 IU/mL, dissolved protein content in the amount of 0.5670 mg/mL, the specific endoglucanase activity of 0.0807 IU/mg and the specific activity of exoglucanase of 0.0123 IU/mg. Keywords: Cellulolytic bacteria, Cellulase enzymes, Enzyme activity, Corn stover